Polypharmacy-induced Drug-Drug Interactions; Threats to Patient Safety - Sharifi, H.; Hasanloei, M. A. V.; Mahmoudi, J. (Drug Research, 2014)
Patient safety is an increasingly recognized challenge and opportunity for stakeholders in improving health care delivery. Because of extensive use of medicines, life expectancy is increasing and elderly as well as comorbidities need polypharmacy, and therefore the risk of drug-drug interactions (DDIs) increases.We searched PubMed and ScienseDirect for epidemiology of articles describing the frequency of potential DDIs published up to 2011 in title, abstract, keywords and text.Studies show that the rate of DDIs both in outpatients and hospitalized patients is high. The elderly, <5 year-old children and women are at higher risks for it. Also, the rate of DDIs in patients who suffer from chronic kidney disease (CKD), cardiovascular disease (CVD) such as heart failure (HF) and hypertension (HTN) and cancers is significant.Physicians, for lowering the risk of DDIs, should take precise drug history, prescribe appropriate and lowest drugs and ultimately counsel with clinical pharmacologist as a key strategy in order to insure the patient safety. This article reviews the existing data concerning this problem to provide an aid for choosing the appropriate drugs and prescribe the most effective with the lowest DDIs for providing patient safety.
Keywords: patient safety; drug-drug interactions; medication errors